2005
DOI: 10.1007/s11136-005-4540-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Indian Patients with Rheumatoid Arthritis

Abstract: The physical domain of HRQOL is most affected in Indian patients with RA. Increasing disease activity and presence of EAMs worsens the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
20
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 26 publications
14
20
2
4
Order By: Relevance
“…In the Iranian studies, the age had a major influence on QOL. As expected, similar to the findings of other studies, older individuals had poorer health status than the younger ones (22,26,27). In the evaluated studies, some items such as high education, higher income, marriage, and occupation were reported as factors improving the patients' QOL.…”
Section: Atapoor Et Al (15) 2002supporting
confidence: 88%
See 2 more Smart Citations
“…In the Iranian studies, the age had a major influence on QOL. As expected, similar to the findings of other studies, older individuals had poorer health status than the younger ones (22,26,27). In the evaluated studies, some items such as high education, higher income, marriage, and occupation were reported as factors improving the patients' QOL.…”
Section: Atapoor Et Al (15) 2002supporting
confidence: 88%
“…In the evaluated studies, there was insignificant association between gender and QOL among patients with RA. These findings were also supported by Bedi et al (27) and Ranzolin et al (21); whereas, the other studies (18,22,28) found the association between gender and QOL. It is important to note that, in all of these studies, female obtained lower scores than male in all domains of QOL (18).…”
Section: Atapoor Et Al (15) 2002supporting
confidence: 75%
See 1 more Smart Citation
“…The same value obtained from a national survey (2) . (13) . Compared to other studies, the scores were lower in the physical and environment domains than people with schizophrenia (physical 57.3 and environment 55.4) and also lower than individuals with acquired immunodeficiency syndrome (physical 67 and environment 63.5) (14) .…”
Section: Discussionmentioning
confidence: 99%
“…12 The socioeconomic status and disability to do work with pain which shows a negative effect on the individuals quality of life and some of the research studies on rheumatoid arthritis suggests that due disease disability and some external factors such as education, gender, social life influences the health related quality of life in rheumatoid arthritis. 8,13 Most patients will have joint destruction, functional impairments and increased mortality having a great impact on patients' Health-Related Quality Of Life (HRQOL) in rheumatoid arthritis. Furthermore, patients have often adapted to their life with RA and have cognitively integrated the illness into their lives by redefining their internal standards of what comprises health, changing their values and priorities and/or redefining the concept of quality of life.…”
Section: Introductionmentioning
confidence: 99%